ChemInform Abstract: A Facile Access to Highly Functionalized Triphenylphosphoranylidene Succinimides Through a Three‐Component Reaction and DFT Investigation of the Reaction Mechanism. Issue 11 (March 2015) - Esmaeili, Abbas Ali; Khoddam‐Mohammadi, Hanieh; Moradi, Abbas; Davamdar, Ehsan; Izadyar, Mohammad; Khavani, Mohammad; Islami, Mohammad Reza
Abstract A novel one‐pot reaction of zwitterions generated in situ from triphenylphosphine and acetylenic esters with aroyl isocyanates affords the title compounds (IV) without using any catalyst or activation.